Remote learning as assessed by students of Collegium Medicum of the Jan Kochanowski University in Kielce (survey questionnaire research) - Mlodawski, Jakub; Mlodawska, Marta; Swiercz, Grzegorz (Journal of Education, Health and Sport, 2022)
During the COVID-19 pandemic in Poland, there was a temporary transition to distance learning at universities. For students of the medical faculty, this change lasted for a shorter than other faculties and was effective until the start of mass vaccinations. For 6 months lectures, seminars, and exercises were held remotely. We conducted an internet-based survey among medical students regarding their assessment of their distance learning experience. We wanted to compare the assessment of students from the first to the third year of studies (group A), who mostly have theoretical classes, and the fourth to sixth (group B), who should mostly have exercises "at the patient’s bedside". Students of the medical faculty (n=82) participated in the survey (62% from group A and 38% from group B). All respondents had free access to a computer and the Internet. We assessed the individual areas of interest in the survey with a five-point Likert scale. There were no differences in the assessment of their own IT competencies among students of both groups. Students of both groups noticed that their level of IT competencies increased in the course of distance learning. The groups differed in terms of the assessment of the level of education offered by the university (4.6 vs 3.2, p <0.05), and the assessment of their own involvement (4.5 vs 3.4, p <0.05). The highest-rated forms of remote learning by students were group work on projects in designated channels of communication with assistants (86% and 78% willingly participate in it). The form assessed to be the worst was teaching based on providing content in electronic form (35% and 42%, respectively, willingly participate in it). The students of the group are less satisfied with the remote classes, which may correspond to the lack of contact with the individual patients. Less satisfaction with the classes conducted leads among students to less involvement on their part.